De l’écriture des marges aux marges de l’écriture - Amélie Pierre (Communication)
Although the social sciences have been viewed according to theoretical and epistemological trends that challenge their positivist posture of neutrality, objectivity, and distance, their methodologies have not been re-examined to the same extent. This article presents the various aspects of the research methodology adopted for the study and shows how these aspects are viable alternatives. First, the article sets out the purpose, the constitution of the field, and the data collection method. The alternative methodologies are then discussed from a pragmatic epistemology perspective to determine how they contribute to the research: perception, engagement, relationships.